2003
DOI: 10.1046/j.1365-3156.2003.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring morbidity in schistosomiasis mansoni: relationship between image pattern, portal vein diameter and portal branch thickness in large‐scale surveys using new WHO coding guidelines for ultrasound in schistosomiasis

Abstract: Summaryobjective World Health Organization consensus meetings on 'Ultrasound in Schistosomiasis' in 1996 and 1997 anticipated further challenges in the global implementation of a standardized protocol for morbidity assessment in schistosomiasis mansoni. We evaluated the performance of the qualitative and quantitative components of the new Niamey criteria.method Use of the Niamey protocol among 3954 subjects in two linked, cross-sectional ultrasound surveys of Schistosoma mansoni-endemic populations in Egypt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 14 publications
5
90
2
1
Order By: Relevance
“…However, the quantitative assessment of periportal thickness of portal vein walls, particularly of the secondary branches, proved to be difficult in everyday use. In addition, it is considered time-demanding and complex, leading to low reproducibility , Hoffmann et al 2001, Richter et al 2001, Ruiz et al 2002, King et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…However, the quantitative assessment of periportal thickness of portal vein walls, particularly of the secondary branches, proved to be difficult in everyday use. In addition, it is considered time-demanding and complex, leading to low reproducibility , Hoffmann et al 2001, Richter et al 2001, Ruiz et al 2002, King et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst clinical investigations with ultrasound and/or abdominal palpation methods can better describe morbidity associated with Schistosoma mansoni infection, for example hepatosplenomegaly, liver fibrosis and/or organ texture (Hatz, 2001;King et al, 2003), these require specialist equipment and well trained staff (Nooman et al, 1995;Ruiz et al, 2002). As a consequence, large-scale community screening of morbidity has been limited and broad geographic comparisons are rarely made.…”
Section: Introductionmentioning
confidence: 99%
“…32 As has been observed in other S. mansoni-endemic countries, the prevalence of fibrosis was shown to increase with increasing age. 20,[32][33][34] We also observed in our study population that adults were more likely to present with portal fibrosis on ultrasound than children. Although this is sometimes reported in children, severe forms of the disease are rarely observed in younger populations.…”
Section: Discussionmentioning
confidence: 57%
“…This finding contrasts with some studies that have that the intensity of infection correlates with disease severity. 20,23,[32][33][34] The lack of association observed in our study could be explained by other possible factors, including the observed high prevalence of S. mansoni infection in this study population, suggesting that the studied participants have repeated exposure.…”
Section: Discussionmentioning
confidence: 96%